Synthesis and Characterization of Some Mannich Base Analogues of Ciprofloxacin: Antibacterial, Antifungal, and Cytotoxic Activities - Rabbani, M. G.; Islam, M. R. (Journal of Scientific Research, 2021)
The present work contains synthesis of six Mannich base analogues of ciprofloxacin 2-7 those have been prepared by the Mannich reaction to investigate some therapeutic assessment. The structure of the analogues has been established by FT-IR, 1H NMR, 13C NMR, mass spectroscopy, and elemental analysis techniques. The derivatives were screened for their antimicrobial activities by the disc diffusion method. The antimicrobial activity of the analogues compared with the parent was evaluated against three Gram-positive, eight Gram-negative bacterial strains, and three different fungal strains. The synthesized compounds showed diverse antimicrobial profiles among which derivatives 2, 3 & 6 possessed enhanced activity in contrast to the ciprofloxacin. Additionally, unlike ciprofloxacin, most of the derivatives were found to demonstrate antifungal activity against Candida albicans. Cytotoxicity was also made against brine shrimp lethality assay. Interestingly, most of the derivatives revealed enhanced cytotoxic activity than that of ciprofloxacin.